Non-Alcoholic Fatty Liver Disease and Hypokalemia in Primary Aldosteronism Among Chinese Population - Chen, Yi; Chen, Xueyang; Chen, Qiang; Yu, Chaohui (Frontiers in Endocrinology, 2021)
Background In recent years, evidence that aldosteronism is a risk factor for metabolic disorders has increased. This study was designed to investigate the role of nonalcoholic fatty liver disease (NAFLD) and hypokalemia in primary aldosteronism (PA). Methods A total of 222 patients diagnosed with PA and 222 non-PA patients were included in our study. Demographic data, medical histories, clinical evaluations, complete blood counts, serum biochemical analyses, aldosterone and potassium levels were obtained. Data are presented as the means ± standard deviation (SD). To compare the parameters between cases and controls, Student’s t-tests or Mann-Whitney U tests were used for continuous variables, and χ2 tests were used for categorical variables. Pearson correlation analysis was used to define relationships between pairs of parameters. A two-sided P < 0.05 was considered statistically significant. Multivariate logistic regression was performed to assess the independent effects of potassium and other metabolic variables on NAFLD in PA patients. Results The diagnosis of NAFLD was more common in PA patients (n=222, 35.1%) than in non-PA subjects (29.7%). PA patients with and without NAFLD had similar metabolic imbalance characteristics. In PA patients with hypokalemia, relatively higher prevalences of NAFLD (44% vs. 27%, P < 0.05) and diabetes mellitus (19.8% vs. 9.9%, P < 0.05) were observed. Hypokalemic PA patients had a worse metabolic status than PA patients without hypokalemia, including higher body mass index (BMI) (25.4 ± 3.4 vs. 24.1 ± 3.9 kg/m2, P < 0.05), more severe dyslipidemia as well as insulin resistance, higher serum uric acid levels (354 ± 95 vs. 319 ± 87 μmol/L, P < 0.01) and aggravated inflammation. Conclusion The prevalence of NAFLD was higher in PA patients than in non-PA patients, although the patterns of obesity, dyslipidemia and insulin resistance were similar. Hypokalemic PA patients had a worse metabolic status than normokalemic PA patients. This study provides new insights that can inform further mechanistic studies about metabolic imbalance in patients with aldosteronism.